(untitled) (Baghdad Science Journal, 2019)
Cutaneous leishmaniasis is a disease caused by Leishmania tropica parasite. Current treatments for this parasite are undesirable because of their toxicity, resistance, and high cost. Macrophages are key players against pathogens. Nitric oxide (NO), a molecule produce by immune cells, controls intracellular killing of pathogens during infection. Silver nanoparticles (Ag NPs) demonstrated broad-spectrum activity against various types of infectious diseases. It has the ability to stimulate oxygen species production. This study aims to analyze the macrophages activation through NO production and estimate the cytotoxicity based on the lactate dehydrogenase (LDH) release upon exposure to L. tropica and Ag NPs. Serially concentrations of Ag NPs were used under two conditions during and following macrophages exposure to L. tropica. MTT assay was used to determine the cytotoxicity of Ag NPs on L. tropica amastigotes during infection of macrophages in vitro. The results showed that by increasing the Ag NPs concentrations, the viability percentage of L. tropica amastigotes decreased and reached to 21.7 ± 0.64 % during infection compared with the control. The 50% inhibitory concentration of Ag NPs on amastigotes was 2.048µg/ml during infection. Moreover, post-phagocytosis study involved the assessment of NO and LDH release by macrophages upon exposure to L. tropica. It have shown that untreated macrophages released low levels of NO while in the presence of Ag NPs, macrophages were activated to produce higher levels of NO under all experimental conditions. On the other hand, macrophages were capable of controlling cytotoxicity and decreasing LDH levels during phagocytosis of L. tropica amastiogotes. Taking together, these findings suggest that Ag NPs can enhance macrophages NO production which provides a method for the identification of Ag NPs ligands with microbicidal and anti-cytotoxic properties against L. tropica pathogens.